Pyrite oxidation and its control : solution chemistry, surface chemistry, acid mine draingae (AMD), molecular oxidation mechanisms, microbial role, kinetics, control, ameliorates and limitations, microencapsulation /: solution chemistry, surface chemistry, acid mine draingae (AMD), molecular oxidation mechanisms, microbial role, kinetics, control, ameliorates and limitations, microencapsulation. ([2018?]) - Evangelou, V. P
No abstract available